MAKNA SUMPAH PALAPA BAGI NUSANTARA - Imam Hadi Sutrisno (Program Studi Pendidikan Sejarah - Universitas Samudra, 2018)
Soekarno once delivered in his speech that the country of the archipelago is a former state power of Majapahit Kingdom. Based on historical facts written in the book ‘Tafsir Negara Kertagama’ there said the archipelago is a former territory of Majapahit. therefore cannot be denied that the Majapahit Kingdom is always identical with the unification of several regions of the archipelago ever initiated by Patih Mahapatih Gajah Mada through the ritual oath. The oath of Mahapatih Gajah Mada is known as the term the ‘Palapa Oath’. It is said that the unification of the archipelago was successfully implemented during the reign of Hayam Wuruk.In this study, researchers will discuss about what is meant by Nationalism and how the form of Nationalism for the nation in Majapahit era, and how the contribution of the meaning of nationalism at this time?The purpose of this research is to develop in patriotic awareness and the highest burden for the nation's children to the state.This study uses descriptive analytical, with historical approach, ie research based on historical facts, and analysis of experts.That nationalism in its outline is the ultimate sacrifice to the state. The meaning of nationalism is essentially a sense of awareness to unite in the container of pluralism. Anderson offers a form of nationalism is an image community.